(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the perioperative risk factors associated with postoperative AKI in patients undergoing cardiac surgery. Methodology: Between January 2011 and December 2017, we analyzed prospectively 544 patients, who were divided into two groups: patients with acute kidney injury associated with cardiac surgery (AKI-ACS) defined as an increase of 0.3 mg/dL or 1.5 times the baseline serum creatinine value and control group formed by patients without AKI-ACS. We compared patients and surgical variables using the chi-square test, Fisher’s exact test, and mann-Whitney test and logistic regression. Results: AKI-ACS occurred in 29.8% of the patients. In the univariate analysis, the following variables presented a statistically significant difference: male gender (p=0.0087), age (p<0.0001), body mass (p=0.035), BMI (p=0.001), thoracic aortic surgery (p=0.029), use of extracorporeal circulation (p=0.012), CPB time (p=0.0001), aortic clamping time (p=0.0029), use of vasoactive drugs in post-operative period (p=0.017), preoperative kidney function (p<0.0001), presence of diabetes mellitus (p=0.008) and NYHA functional class (p=0.041). In the multivariate analysis, the following variables presented a statistical difference: male gender (OR 2.11), higher BMI (OR 2.11), worse preoperative renal function, demonstrated by creatinine clearance (OR 0.13), longer cardiopulmonary bypass (OR 1.008). Conclusion: The independent predictors for LRA-ACC were male gender, higher body mass index, worse preoperative renal function, and more complex surgeries associated with longer cardiopulmonary bypass.